Investigating the Synergistic Effect of Silver Nanoparticles With Third-Generation Cephalosporins Against Acinetobacter baumannii - Luzell Senobia Britz; Abdulrahman M. Elbagory; Oladipupo Moyinoluwa David; Mervin Meyer; Charlene W. J. Africa (Journal of Nanotechnology)
The antibacterial activity of nanoparticles has been explored to overcome the rising microbial resistance against antibiotics. The purpose of this study was to synthesize epigallocatechin-3-gallate silver nanoparticles (EGCG-AgNPs) and evaluate their antibacterial activity alone and in combination with third-generation cephalosporins on a multi–drug-resistant strain of Acinetobacter baumannii. EGCG-AgNPs were characterized using ultraviolet-visible spectroscopy (UV–Vis), dynamic light scattering (DLS), high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The combined activities of EGCG-AgNPs with ceftazidime (CAZ), cefotaxime (CTX) and ceftriaxone (CRO) were evaluated using the checkerboard method, and the results were interpreted as synergistic, antagonistic or indifferent. The findings showed that EGCG-AgNPs were successfully synthesized and showed an absorbance peak at 410 nm, hydrodynamic diameter of ±22.21 nm, PDI of 0.200 and zeta potential of −27.8 mV. HRTEM showed spherical AgNPs, XRD confirmed the crystalline structure, and FTIR analysis indicated the involvement of the hydroxyl, carboxyl and amine groups in the synthesis of the AgNPs. The minimum inhibitory concentration (MIC) of the antibiotics alone was 125 μg/mL for all three antibiotics, while the MIC of the EGCG-AgNP was 250 μg/mL. Synergy with the AgNPs was observed for all three antibiotics, with a fractional inhibitory concentration (FIC) index of 0.0656, 0.064 and 0.06327 μg/mL, for CAZ, CTX and CRO, respectively. The results of the study showed the antibacterial potential of EGCG-AgNPs and their role in circumventing Acinetobacter baumannii resistance to third-generation cephalosporins.